Effect of Tb3+ doping in mixed-valence manganites and cobaltites. (30th August 2017) - Knížek, K; Jirák, Z; Kaman, O; Maryško, M; Damay, F
Abstract: The magnetic ordering of four Tb 3+ -doped manganites and cobaltites, La0.7 Tb0.1 Sr0.2 MnO3, La0.7 Tb0.1 Ca0.2 MnO3, La0.7 Tb0.1 Sr0.2 CoO3 and La0.7 Tb0.1 Ca0.2 CoO3, have been studied by means of neutron diffraction and SQUID magnetometry. All the samples were prepared by sintering of sol–gel precursors and their orthorhombic or rhombohedral perovskite structures at room and low temperatures were refined. A long-range ferromagnetic (FM) order was detected at the Mn and Co sites. In addition, a small but significant ordered moment was observed at A sites of studied cobaltites, which was attributed to local Tb 3+ moments, aligned by exchange interactions due to FM ordered Co sublattice. No or minor Tb 3+ contribution was detected in studied manganites.